THE CONCEPT OF WASILAH IN THE QUR’AN: ANALYSIS OF TAFSĪR MAQĀSIDI’S OF QS. AL-MĀIDAH [5]: 35 AND QS. AL-ISRĀ’ [17]: 57 - Fithrotin, Fithrotin; Muttaqin, Khusnul; Wahid, Najihah Abd (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2023)
In navigating life cannot be separated from a problem, the problems of Muslims are also different, both problems regarding themselves or problems from social aspects. Wasilah is a term used by Muslims as an intermediary to pray to Allah so that their prayers will be answered and their needs can be resolved. The majority of Muslims in understanding wasilah tend to give meaning as a means of intermediary, namely making certain things to be intermediaries to Allah.Wasilah is not something that must be done nor is it a cause for prayer to be answered, but the most important and essential thing is to pray absolutely to Allah. The term wasilah is also explained in Q.S al-Maidah verse 35 and Q.S al-Isra’ verse 57. This research uses descriptive qualitative method with maqashidi interpretation approach. Checking the validity is done by looking directly at the text of the book or the original book which discusses the interpretation of Q.S al-Maidah verse 35 and al-Isra' verse 57. The results of the study found: aspects of maqasid hifzu din and hifzu nafs as well as human values and values of responsibility